Understanding the Effect of Advertising Values on Sustainable Product Purchase Intention: Extended Ducoffe Advertising Value Model - Nornajihah Nadia Hasbullah; Zurina Patrick; Hainnuraqma Rahim; K. K. Ramachandran (Human Resource Management Academic Research Society, 2023)
Following the advertising value model by Ducoffe, this study develops a conceptual framework, which provides several insights. First, three variables consist of informativeness, entertainment, and irritation of advertisement will be directly influencing purchase intention. Secondly, the researcher developed the mediator interaction to reveal the effect of the source of advertisements on influencer credibility between advertising value and sustainable product purchase intention. To address the research objective, an online survey will be carried out based on quantitative research methods. By using a purposive sampling, the Millennial generation were selected as a respondent. Meanwhile, the researcher will analyse data by using PLS SEM. The study was expected to be significant for all the variables. In hence, this study would be benefit for companies and digital marketers to deeply understand how customer view social media advertisement and create more effective advertisement structure.